2014
DOI: 10.1159/000359972
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke Exposure in Pulmonary Arterial and Thromboembolic Pulmonary Hypertension

Abstract: BACKGROUND: Animal studies and data from a single-center study suggest that tobacco smoke exposure may be a risk factor for precapillary pulmonary hypertension (PH). OBJECTIVE: We aimed to survey tobacco smoke exposure in a large PH collective and to compare it with epidemiological data from healthy subjects. METHODS: This is an international, multicenter, case-control study including patients with pulmonary arterial and chronic thromboembolic PH. All patients were asked specific questions about tobacco smoke … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
(43 reference statements)
1
23
0
Order By: Relevance
“…The physiological changes caused by the aging process, the chronic presence of hypertension ( 55 ), and the influence caused by the pharmacological treatment ( 54 ) could reduce the statistical benefits of exercise for BP. Moreover, it is also known that PEH is a multifactorial phenomenon, influenced by biological (e.g., sex, age, ethnicity, and genetics), behavior (e.g., excessive alcohol consumption, smoking, low levels of physical activity, and hyper sodic and hyper caloric diets), and socioeconomic (e.g., purchasing power and educational level) factors ( 56 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological changes caused by the aging process, the chronic presence of hypertension ( 55 ), and the influence caused by the pharmacological treatment ( 54 ) could reduce the statistical benefits of exercise for BP. Moreover, it is also known that PEH is a multifactorial phenomenon, influenced by biological (e.g., sex, age, ethnicity, and genetics), behavior (e.g., excessive alcohol consumption, smoking, low levels of physical activity, and hyper sodic and hyper caloric diets), and socioeconomic (e.g., purchasing power and educational level) factors ( 56 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Chaouat et al [8], severe PH was present in a subgroup of patients with mild airway obstruction and severe hypoxemia with very low diffusing capacity for carbon monoxide. Pulmonary artery vasoconstriction induced by alveolar hypoxia is considered to contribute to mild to moderate PH in COPD [11,12], but cigarette smoke [13] and inflammation (i.e. IL-6) [14] may also play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco smoke exposure can lead to an elevation of pulmonary artery pressure, long before destruction of the lung parenchyma [3234]. Keusch et al observed a significantly higher smoking prevalence in PH men and significantly more exposure to tobacco smoke in PH women to in a case-control study [35]. Another study in hemodialysis patients also found that PH was related to cigarette smoking [36].…”
Section: Discussionmentioning
confidence: 99%